2020
DOI: 10.1111/jcmm.15591
|View full text |Cite
|
Sign up to set email alerts
|

miR‐30b Promotes spinal cord sensory function recovery via the Sema3A/NRP‐1/PlexinA1/RhoA/ROCK Pathway

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Interestingly, miR-30b was found to be significantly upregulated in hippocampal tissues of AD patients and rat models ( Li et al , 2020a ; Song et al , 2019 ), and in plasma samples of Parkinson’s disease patients ( Brennan et al , 2019 ), further supporting the fact that miRNA regulation can be differentially regulated based on the model, disease context, or even sample matrix. In vitro, similar to our study, inhibition of miR-30b resulted in a decrease in neurite length of rat primary sensory neurons ( Wang et al , 2020 ). miR-30d, which was downregulated upon exposure to COL and DOX in our study, was also downregulated in blood samples of acute ischemic stroke patients and in CSF samples of AD patients ( Brennan et al , 2019 ; Jiang et al , 2018 ).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Interestingly, miR-30b was found to be significantly upregulated in hippocampal tissues of AD patients and rat models ( Li et al , 2020a ; Song et al , 2019 ), and in plasma samples of Parkinson’s disease patients ( Brennan et al , 2019 ), further supporting the fact that miRNA regulation can be differentially regulated based on the model, disease context, or even sample matrix. In vitro, similar to our study, inhibition of miR-30b resulted in a decrease in neurite length of rat primary sensory neurons ( Wang et al , 2020 ). miR-30d, which was downregulated upon exposure to COL and DOX in our study, was also downregulated in blood samples of acute ischemic stroke patients and in CSF samples of AD patients ( Brennan et al , 2019 ; Jiang et al , 2018 ).…”
Section: Resultssupporting
confidence: 89%
“…Inhibiting miR-30b was shown to decrease the neurite length, likely mediated by miR-30b targeting Sema3A/RhoA pathway, which is an important regulator for axonal growth ( Wang et al , 2020 )…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo treatment with miR-30b agomir, following the results of the in vitro study, demonstrated that miR-30b agomir promoted axon growth by regulating the Sema3A/PlexinA1-NRP-1/RhoA pathway/ROCK. This also improved sensory conductive function after spinal cord dorsal column lesion [ 122 ].…”
Section: Mirnas For Neuronal Regeneration In Scimentioning
confidence: 99%
“…Sema3A binds to the receptor complex containing PlexinA1 and Neuropilin-1 (NRP-1) and modulates the Rho/ROCK pathway [ 119 ]. Wang et al investigated whether miR-30b, which targets sema3A to promote retinal ganglion cell neurite growth [ 120 ], could exert primary sensory neuron neurite outgrowth after SCI [ 121 ]. They found that the up-regulation of miR-30b inhibited sema3A expression and RhoA/ROCK activity through the PlexinA1/NRP-1 co-receptor, promoting primary sensory neuron neurite outgrowth and spinal cord sensory conductive function recovery ( Table 2 and Figure 3 ).…”
Section: Rho/rock Pathway and Mirnas For Apoptosis/axon Regeneration In Scimentioning
confidence: 99%